2014
DOI: 10.1063/1.4866577
|View full text |Cite
|
Sign up to set email alerts
|

High performance transistors via aligned polyfluorene-sorted carbon nanotubes

Abstract: We evaluate the performance of exceptionally electronic-type sorted, semiconducting, aligned single-walled carbon nanotubes (s-SWCNTs) in field effect transistors (FETs). High on-conductance and high on/off conductance modulation are simultaneously achieved at channel lengths which are both shorter and longer than individual s-SWCNTs. The s-SWCNTs are isolated from heterogeneous mixtures using a polyfluorene-derivative as a selective agent and aligned on substrates via dose-controlled, floating evaporative sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 38 publications
2
90
0
Order By: Relevance
“…[15][16][17][18][19][20][21] Since these networks are normally thin and comprised of singlewalled CNTs that are 50 µm long, [15][16][17][18][19][20][21] our understanding of the impact of morphology on electron transport in thick CNT networks comprised of long ( 100 µm) multiwalled CNTs remains incomplete. Recent work on A-CNT networks made via roller densification of 100 µm long vertically aligned CNT arrays showed that the sheet resistance is directly proportional to the density of the network, 22 and is mildly anisotropic in nature.…”
Section: 2mentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Since these networks are normally thin and comprised of singlewalled CNTs that are 50 µm long, [15][16][17][18][19][20][21] our understanding of the impact of morphology on electron transport in thick CNT networks comprised of long ( 100 µm) multiwalled CNTs remains incomplete. Recent work on A-CNT networks made via roller densification of 100 µm long vertically aligned CNT arrays showed that the sheet resistance is directly proportional to the density of the network, 22 and is mildly anisotropic in nature.…”
Section: 2mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] Each of these techniques is able to separate SWNTs into metallic and semiconducting species in different level of success. In spite of their promises, each method has its own limited capability to scale up or requires a complex process of removing the surfactants or polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Particularly, the high charge-carrier mobility of semiconducting SWNTs has a promising prospect for FETs. [7] However, SWNTs are generally produced as a mixture of semiconducting SWNTs (s-SWNTs) and metallic SWNTs (m-SWNTs) which is a barrier for the application in electronic fields. Although some research has been done to directly synthesize chiral selective nanotubes, the purity and yield of s-SWNTs are not satisfied.…”
mentioning
confidence: 99%
“…20,21,25 All transistors exhibit noticeable operating hysteresis ($3.4 V) and is attributed to the presence of surface adsorbates and water on the Al 2 O 3 surface. 11,26 Despite this, all devices exhibit low operating voltages (<j10jV), appreciable channel current on/off ratio (I ON /I OFF > 10 3 ), low threshold voltage (V TH $ À1.1 V), a sub-threshold swing (SS) of $1.73 V/dec, and linear (l LIN ) and saturation (l SAT ) hole mobilities of 0.7 cm 2 V À1 s À1 , 2.3 cm 2 V À1 s À1 , respectively.…”
mentioning
confidence: 99%
“…5,[8][9][10][11][12] Using such intrinsically simple approaches, flexible transistors and complementary logic circuits based on a solution-deposited random network of SWNTs have recently been reported. 8,13,14 Among the various processing methods available, drop-cast, 5 dip-coating, 8 inkjet printing, 9 blade coating, 10 self-assembly, 11 and gravure printing 12 have proven suitable for large-area deposition of SWNTs at room temperature. However, purifying and sorting semiconducting SWNTs from metallic CNTs and/or catalyst residues before deposition is technologically challenging but of crucial importance for numerous device applications.…”
mentioning
confidence: 99%